Simulation and dynamical analysis of freeway traffic - Figueiredo, Lino (2003)
This paper discusses the problem of modelling and simulation of traffic systems, and presents the traffic simulator SITS (Simulator of Intelligent Transportation Systems). The SITS is based on a microscopic simulation approach considering different types of vehicles, drivers and roads. A dynamical analysis of several traffic phenomena is then addressed.